FEATURES OF ESCHERICHIA COLI CLINICAL STRAINS, ISOLATED FROM THE PATIENTS WITH CROHN’S DISEASE - R. B. Gorodnichev; D. V. Rakitina; A. I. Manolov; Yu. P. Baykova; P. L. Scherbakov; G. B. Smirnov; E. N. Ilina (Журнал микробиологии, эпидемиологии и иммунобиологии, 2017)
Aim. To characterize pool of Crohn’s disease-associated E.coli isolated from patients with Crohn’s disease. Materials and methods. 28 clinical stains were selected. Clinical isolates, as well as control samples, were tested for their possible belonging to a certain phylogenetic group, the ability to adhere and invade on the model of a monolayer of CaCo2 epithelial cells, the ability to form biofilms and their mobility. Results. We have shown that E.coli, isolated from a different biomaterial, belonged to different phylogenetic groups and differed in their ability to form biofilms. Adhesive-invasive E.coli were found mainly in the material of biopsy of the intestinal mucosa of patients with Crohn’s disease. Conclusion. There are reasons to suppose that adhesive-invasive E.coli formed at the junction of ecological niches of the lumen and the intestinal wall.